EVALUASI PENERAPAN CARA PRODUKSI PANGAN OLAHAN YANG BAIK (CPPOB) DI LIVIA CATERING YOGYAKARTA: Evaluation of The Application of Good Manufacturing Practices (GMP) at Livia Catering Yogyakarta - Citra Mutiara Putri; Ika Dyah Kumalasari (Universitas Darussalam Gontor, 2022)
Food safety is very important to prevent foodborne illness. Because safe, quality, and minimally contaminated food can be realized by the food industry with good processing and clean environmental management. In small industries such as catering, it is often inconsistent with implementing good food processing methods and ensuring food quality and safety. Data was collected through interviews, observations, and documentation, as well as filling out a checksheet based on the Regulation of the Minister of Industry of the Republic of Indonesia No. 75/MIND/PER/2010, then analyzed using fishbone diagrams. Based on the results of the analysis, it can be seen that there are deviations in the GMP in 7 of the 18 aspects. The deviation consists of aspects of the building and production space; sanitation facilities; the final product; laboratory; employees; maintenance and sanitation programs; and implementation of these guidelines. From these 7 aspects, it is known that there are 12 discrepancies with a percentage of 15.7%. Appropriate aspects include production locations and sites, machinery and equipment, materials, process control, packaging, labeling, storage, transportation, documentation and record keeping, employee training, and product recalls. The resulting percentage from the suitability aspect is 84%. People, procedures, and facilities are obstacles that hinder the implementation of GMP.